Elective versus emergency caesarean section: differences in maternal outcome - Sharma, Anshu; Acharya, Rajiv; Pehal, Yashika; Sharma, Bhawna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section is a life-saving surgical procedure when certain complications arise during pregnancy or labour. The use of CS worldwide has increased worldwide unprecedented levels although the gap between higher- and lower-resource settings remains. The present study evaluates the difference in maternal outcome in elective versus emergency caesarean sections in our institute. Methods: The study included first 65 cases of emergency caesarean section (group A) and during the study period, first 65 elective caesarean section (group B) if they fulfilled the inclusion criteria. Various intra operative and postoperative events were recorded which included intra operative complications, postpartum haemorrhage and transfusion indices. Results: The most common indication of caesarean section in group A was fetal distress (27.7%). In group B most caesarean sections were classified under 5 followed by class 6, the most common indication being previous caesarean section (27.6%). It was observed that pre-operative mean haemoglobin in group A was 10.6 g/dl and in group B was 11.2g/dl. A drop of 1.36 g/dl in group A and 1.10 g/dl in group B was observed in the post-op period. Cross match / transfusion ratio 1.5 in group A and 2 in group B, transfusion probability ratio was 60 % in group A and 66.7% in group B and transfusion index was 1 in group A and group B. There was significantly higher contraception acceptance in group B compared to group A. Conclusions: Elective caesarean section has more favourable maternal outcome as compared to emergency caesarean section as the former is done under controlled and planned circumstances. However, there should be stringent audit to scrutinise indication of caesarean section, outcome of caesarean and blood transfusion practices.